2016
DOI: 10.1021/acs.biochem.6b00164
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes Associated with Transthyretin Misfolding and Amyloid Formation Revealed by Solution and Solid-State NMR

Abstract: Elucidation of structural changes involved in protein misfolding and amyloid formation is crucial for unraveling the molecular basis of amyloid formation. Here we report structural analyses of the amyloidogenic intermediate and insoluble aggregates of transthyretin (TTR) using solution and solid-state NMR spectroscopy. Our solution NMR results show that one of the two main β-sheet structures (CBEF β-sheet) is maintained in the aggregation-competent intermediate, while the other DAGH β-sheet is more flexible on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 26 publications
5
60
0
Order By: Relevance
“…19,20 In particular, the native CBEF β-sheet remains unchanged in the amyloidogenic intermediate state of TTR, while the other β-sheet (DAGH) undergoes conformational fluctuations in millisecond time scales. The structural feature of the aggregation-prone states of TTR was investigated with CD spectroscopy (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 In particular, the native CBEF β-sheet remains unchanged in the amyloidogenic intermediate state of TTR, while the other β-sheet (DAGH) undergoes conformational fluctuations in millisecond time scales. The structural feature of the aggregation-prone states of TTR was investigated with CD spectroscopy (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, our recent solid-state NMR experiments showed that TTR amyloid used in this study is a uniform protein assembly consisting of a single monomeric core conformer. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous solid-state studies revealed that the native-like CBEF and DAGH β-structure is retained in WT TTR amyloid state, while AB loop regions that are hydrogen-bonded with strand A undergo a structural transition. 33 The partly exposed strand A might be involved in intermolecular interactions essential to TTR amyloid formation. In our present solid-state NMR studies reported here, the amyloid states of the two TTR variants are also shown to adopt the similar native-like CBEF and AGH β-sheet structure.…”
Section: Discussionmentioning
confidence: 99%
“…The TTR amyloid was examined by transmission electron microscopy (TEM) and thioflavin T (ThT) binding assay in our previous studies. 33 …”
Section: Methodsmentioning
confidence: 99%